THE INFLUENCE OF HYPNOTEACHING STRATEGY AND READING MOTIVATION TOWARD STUDENTS’ READING ABILITY - Vira Zalika; Tahrun Tahrun; Artanti Puspita Sari (Universitas PGRI Palembang, 2022)
This study concerned with the influence of hypnoteaching strategy and reading motivation towards students’ reading ability. This study applied 2x2 (two by two) factorial design method. The sample was 60 students that divided into two groups. There were 30 students as experimental group and 30 students as control group. The data were collected by using a questionnaire and written test with multiple choice questions that analyzed by using t-test and two-ways Anova. The findings showed that (1) there was significant different in reading ability between the students who had high reading motivation and low reading motivation taught by using hypnoteaching strategy and no experimental treatment (2) there are interaction effects of hypnoteaching strategy and no experimental treatment, and (3) hypnoteaching strategy can be utilized to promote and contributes the reading ability of the students. It could be concluded that hypnoteaching strategy and reading motivation showed significant role to improve students’ reading ability on narrative text.